2017
DOI: 10.1113/jp273626
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical effects of calcium‐sensitive potassium currents on voltage and calcium alternans

Abstract: Cardiac alternans is a precursor to life-threatening arrhythmias. Alternans can be caused by instability of the membrane voltage (V ), instability of the intracellular Ca ( Ca i2+) cycling, or both. V dynamics and Ca i2+ dynamics are coupled via Ca -sensitive currents. In cardiac myocytes, there are several Ca -sensitive potassium (K ) currents such as the slowly activating delayed rectifier current (I ) and the small conductance Ca -activated potassium (SK) current (I ). However, the role of these currents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 52 publications
(116 reference statements)
1
27
0
Order By: Relevance
“…Intracellular Ca 2+ also affected V m oscillations. Thus, in ventricular myocytes, a modeling study indicated that increasing [Ca 2+ ] i would prolong the oscillation period at baseline SK currents but reduce it at higher current levels (Kennedy, Bers, Chiamvimonvat, & Sato, ). Taken together, the spatiotemporal characteristics of intracellular Ca 2+ and V m oscillations, dependent on the tissue specificity of the associated K Ca current(s), could direct the resulting differentiation.…”
Section: Ca2+‐activated K+ Channels and Ca2+ Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular Ca 2+ also affected V m oscillations. Thus, in ventricular myocytes, a modeling study indicated that increasing [Ca 2+ ] i would prolong the oscillation period at baseline SK currents but reduce it at higher current levels (Kennedy, Bers, Chiamvimonvat, & Sato, ). Taken together, the spatiotemporal characteristics of intracellular Ca 2+ and V m oscillations, dependent on the tissue specificity of the associated K Ca current(s), could direct the resulting differentiation.…”
Section: Ca2+‐activated K+ Channels and Ca2+ Signalingmentioning
confidence: 99%
“…Intracellular Ca 2+ also affected V m oscillations. Thus, in ventricular myocytes, a modeling study indicated that increasing [Ca 2+ ] i would prolong the oscillation period at baseline SK currents but reduce it at higher current levels (Kennedy, Bers, Chiamvimonvat, & Sato, 2016).…”
Section: Figurementioning
confidence: 99%
“…It is now well recognized that an important component of Na + channel regulation is due to Ca 2+ , calmodulin (CaM) and CaM-dependent protein kinase II (CaMKII) pathway that affects channel function [55]. L-type Ca 2+ (ICaL) and sodium(Na + )-Ca 2+ exchanger currents are Ca 2+ -sensitive, as well as the slowly activating delayed rectifier current IKs, which plays an important role in regulating action potential duration [56]. Although in this work we did not perform electrophysiological measurements on isolated ventricular myocytes, we can speculate on the potential effects of increased SERCA2 activity, based on several findings reported in the present study.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Either approach seeks to demonstrate arrhythmogenesis at the systems level and then to resolve underlying cellular mechanisms in the corresponding model system. An important computational study in this Journal of Physiology issue (Kennedy et al 2017) investigated effects of the Ca 2+ -activated, slowly activating delayed rectifier and small conductance potassium (SK) channels, respectively carrying I Ks and I SK , on pro-arrhythmic instabilities producing AP duration (APD) alternans. Such alternans can reflect membrane potential (V m (t)) instabilities from steep dependences of APD restitution upon diastolic interval (DI) and are known clinically to presage major ventricular arrhythmias.…”
mentioning
confidence: 99%